Comprehensive identification of non-volatile bitter-tasting compounds in Zanthoxylum bungeanum Maxim. by untargeted metabolomics combined with sensory-guided fractionation technique. (15th June 2021) - Yang, Qingqing; Mei, Xiaofei; Wang, Zhirong; Chen, Xuhui; Zhang, Rui; Chen, Qiaoli; Kan, Jianquan
Graphical abstract: Highlights: 37 potentially bitter metabolites were screened in Gou Jiao by untargeted metabolomics. Some possible mechanisms of bitterness formation in Z. bungeanum were proposed. 15 bitter compounds were identified through sensory-guided chromatographic fractionation. Novel basis to understand the bitterness chemistry in Z. bungeanum was established. Abstract: Zanthoxylum Bungeanum Maxim. is an important seasoning in Chinese cooking, but its bitter taste limits its use by some consumers. In this study, metabolomic analysis based on ultra-high-performance liquid chromatograph–tandem mass spectrometry (UPLC–MS) was used to screen out a vast number of potential non-volatile bitter compounds in Z. bungeanum. Results showed that there were 37 potential bitter compounds in Z. bungeanum, and possible mechanisms underlying its bitter taste were provided. Further, instrumental analyses combined with sensory evaluation were used to identify the key bitter compounds in Gou jiao, a wild variant of Z. Bungeanum with a strong bitter taste. Totally 15 key bitter compounds were identified, most of which have a low bitterness recognition threshold. This study is the first comprehensive identification of non-volatile bitter compounds in Z. bungeanum and provides a basis for future investigations into mitigating bitterness and uncovering how the interaction between different bitter compounds affects taste.